2009
DOI: 10.1080/09658210902939322
|View full text |Cite
|
Sign up to set email alerts
|

Examining the life story account of the reminiscence bump: Why we remember more from young adulthood

Abstract: The reminiscence bump is a robust finding demonstrated mostly with the cue-word method in Western cultures. The first aim of the study was to replicate the reminiscence bump using a life history timeline method and to extend reminiscence bump research to a Turkish sample. The second aim was to empirically examine the recently proposed life story account (Gluck & Bluck, 2007) for the reminiscence bump. The sample consisted of 40 women and 32 men aged 52 to 66 years. Participants' lives were divided into 5-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
73
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(81 citation statements)
references
References 33 publications
6
73
1
1
Order By: Relevance
“…Most notably, in looking at memories of important events, Glück and Bluck (2007) found that, similar to Rubin and Berntsen (2003), only positive events evinced a bump. However, in particular support of the life story account, the bump was only found in positive events over which the individual had a high level of perceived control (for related findings, see Demiray et al, 2009). One limitation of this finding, though, is that, as Glück and Bluck's framework suggests, emotional valence and perceived control are not strictly independent dimensions, as events over which the individual had a high level of perceived control were disproportionately positive.…”
Section: Mechanisms Underlying the Bump In Autobiographical Memorymentioning
confidence: 74%
See 3 more Smart Citations
“…Most notably, in looking at memories of important events, Glück and Bluck (2007) found that, similar to Rubin and Berntsen (2003), only positive events evinced a bump. However, in particular support of the life story account, the bump was only found in positive events over which the individual had a high level of perceived control (for related findings, see Demiray et al, 2009). One limitation of this finding, though, is that, as Glück and Bluck's framework suggests, emotional valence and perceived control are not strictly independent dimensions, as events over which the individual had a high level of perceived control were disproportionately positive.…”
Section: Mechanisms Underlying the Bump In Autobiographical Memorymentioning
confidence: 74%
“…For instance, in the important memories method, researchers have asked participants to report x number of important memories (or the x most important memories) in their lives (Glück & Bluck, 2007;Haque & Hasking, 2010;Rubin & Schulkind, 1997). Similarly, researchers have asked participants to report the memories they consider to be most central to their life story (Bohn, 2010;Thomsen & Berntsen, 2008), or to simply freely recall autobiographical memories, which appears to yield a focus on important memories (Conway & Holmes, 2004;Demiray, Gülgöz, & Bluck, 2009;Howes & Katz, 1992;Rabbitt & Winthorpe, 1988).…”
Section: The Reminiscence Bump In Autobiographical Memorymentioning
confidence: 96%
See 2 more Smart Citations
“…Janssen and Murre 2008;Rubin et al 1998). In fact, the more recently proposed life story account (Glück and Bluck 2007) integrates central components of these accounts by hypothesising that the reminiscence bump period includes more novel, more distinctive, more self-relevant, and more transitional events than other life periods (Demiray et al 2009). In the present study, we do not aim to test these different accounts against each other but to examine whether the distribution of AMs varies according to the functions that these long-term memories still serve in daily life.…”
Section: Introductionmentioning
confidence: 99%